High-Definition Differential Ion Mobility Spectrometry with Resolving Power up to 500 - Shvartsburg, Alexandre A. (2012)
As the resolution of analytical methods improves, further progress tends to be increasingly limited by instrumental parameter instabilities that could be ignored before. This is now the case with differential ion mobility spectrometry (FAIMS), where fluctuations of the voltages and gas pressure have become critical. A new high-definition generator for FAIMS compensation voltage reported here provides a stable and accurate output than can be scanned with negligible steps. This reduces the spectral drift and peak width, thus improving the resolving power (R) and resolution. The gain for multiply-charged peptides that have narrowest peaks is up to ~40%, and R ~ 400 – 500 is achievable using He/N(2) or H(2)/N(2) gas mixtures.